Implementation and Costs of the Certified Community Behavioral Health Clinic Demonstration. (20th August 2020) - Brown, J.; Breslau, J.; Siegwarth, A.; Miller, R.; Kase, C.; Dunbar, M.; Briscombe, B.; Dey, J.
Abstract : Research Objective: Medicaid has historically reimbursed community mental health centers using fee‐for‐service or negotiated managed care rates that did not always cover the full costs of the services provided by these clinics. To address this problem and improve quality of care, eight states implemented the Certified Community Behavioral Health Clinic (CCBHC) Demonstration—the first large‐scale test of Medicaid value‐based payment for community mental health centers. Clinics that became CCBHCs received a fixed daily or monthly prospective Medicaid payment set by the state to cover the full costs of nine required types of services. CCBHCs were expected to adhere to staffing and care coordination requirements, increase access to care, and report quality measures that could be used to award bonus payments. This presentation describes how CCBHCs expanded services; the extent to which payment rates covered costs; and how states and CCBHCs used quality measures. Study Design: We conducted a mixed‐methods evaluation that included surveying CCBHCs in both demonstration years, three rounds of interviews with state Medicaid and behavioral health officials, and analysis of cost reports submitted by CCBHCs. Population Studied: Sixty‐six CCBHCs serving an estimated 330, 000 individuals with behavioral health conditions in the first demonstration year. Principal Findings: Nearly all clinics hired staff (particularly nurses, substance use disorder specialists, case managers, and peer specialists) and 84% expanded services to become CCBHCs; 63% added some type of mental health or substance use service, 55% added psychiatric rehabilitation services, 51% added crisis services, 46% added medication assisted treatment for alcohol or opioids, and 42% added primary care screening and monitoring. To expand access, CCBHCs instituted same‐day scheduling, provided services outside of clinic locations, and developed collaborations with community providers. CCBHC payment rates varied widely within and across states during the first year. Daily rates ranged from 151 to 667, and monthly rates ranged from 558 to 902. Rates were driven by population density, client volume, and staffing mix. In seven of the eight states, the per‐day or per‐month cost of CCBHC services during the first year was, on average, 8% to 32% lower than the cost estimated by the state prior to the demonstration; costs were lower than anticipated for 80% of CCBHCs but higher than anticipated for 20%. Differences between estimated and actual costs were due in part to uncertainty about the volume of CCBHC services and the cost of new services. States and CCBHCs used quality measures to inform changes in their service delivery. All but one state used quality measures to award bonus payments but states established very different bonus performance thresholds. Conclusions: Clinics engaged in significant transformation to become CCBHCs. Despite expanding services and hiring staff, costs in the first year were, on average, lower than states' original estimates but the extent to which the payment rate covered clinic costs varied considerably by clinic. Implications for Policy or Practice: Stakeholders seeking to replicate the CCBHC model should expect that clinics will need to undertake substantial expansion of services and hire staff to meet CCBHC requirements. Payment rates may need adjustment over time as clinics gain experience with new services and populations. Primary Funding Source: U.S. Department of Health and Human Services, Office of the Assistant Secretary for Planning and Evaluation.